2019
DOI: 10.1016/j.cose.2019.101602
|View full text |Cite
|
Sign up to set email alerts
|

A secure and auditable logging infrastructure based on a permissioned blockchain

Abstract: Information systems in organizations are regularly subject to cyber attacks targeting confidential data or threatening the availability of the infrastructure. In case of a successful attack it is crucial to maintain integrity of the evidence for later use in court. Existing solutions to preserve integrity of log records remain cost-intensive or hard to implement in practice. In this work we present a new infrastructure for log integrity preservation which does not depend upon trusted third parties or specializ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…e construction of a national smart grid industry not only involves social issues such as people's livelihood and national defense but also shows the strength of the new energy strategy, which promotes the application of blockchain technology to social and environmental problems. Blockchain technology can reduce economic costs to a large extent, which will make it easier to control financial costs [30], reduce power generation production costs, and improve power infrastructure utilization efficiency [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e construction of a national smart grid industry not only involves social issues such as people's livelihood and national defense but also shows the strength of the new energy strategy, which promotes the application of blockchain technology to social and environmental problems. Blockchain technology can reduce economic costs to a large extent, which will make it easier to control financial costs [30], reduce power generation production costs, and improve power infrastructure utilization efficiency [21].…”
Section: Discussionmentioning
confidence: 99%
“…Auditing cost control has always been a major concern of national auditing departments. Processing audit data through blockchain technology can effectively control auditing costs [30].…”
Section: Financial Cost Managementmentioning
confidence: 99%
“…Audit logs are themselves a key target for an attacker who needs to erase any trace of their malicious activities; otherwise, they may get caught and then possibly prosecuted. The need for securing audit logging was raised already in different contexts, including hardware [3]; systems [4,5]; file systems [6]; databases [7]; secure logging protocols [8]; distributed systems [2,[10][11][12][13][14]; blockchain [1,[16][17][18][19][20]; and blockchain hardware [28], as well as many others. In this section, we describe some pieces of research in securing audit logging, with particular attention on distributed systems and cloud computing; we describe blockchain-based mechanisms later in the following subsection.…”
Section: Audit Based Systemsmentioning
confidence: 99%
“…Chowdhury et al presented an analysis, reporting that blockchain can be applied to more critical scenarios [15]. Due to the transparency offered by blockchain technology, there is an increasing number of new mechanisms that use this technology for audit logging [1,[16][17][18][19][20]. We have found that these solutions, however, do not show enough detail about how the transactions are formed through smart contracts.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our work, however, they focused on the case where other 'miners' (peer-to-peer nodes) are themselves the malicious attackers whereas we focus on securing the logs from an attacker outside the blockchain. Another closely related recent work [28] considered using a blockchain to store log files though there the authors used different frameworks and made alternative choices from those we make here [29].…”
Section: Prior Workmentioning
confidence: 99%